44.2k views
4 votes
Which identity resulted from the proof in part A, which showed that a triangle with side lengths x2 − 1, 2x, and x2 + 1 is a right triangle?

User Marshal
by
6.2k points

2 Answers

5 votes

Answer:

(x2 − 1)2 + (2x)2 = (x2 + 1)2

Explanation:

for PLATO users this is the right answer

User Exia
by
6.0k points
4 votes

we know that

In a right triangle

Applying the Pythagorean Theorem


hypotenuse^(2) =leg1^(2) +leg2^(2)

In this problem

Let


hypotenuse=x^(2) +1\\leg1=2x\\ leg2=x^(2) -1

substitute in the formula above


hypotenuse^(2) =leg1^(2) +leg2^(2)


(x^(2) +1)^(2) =(2x)^(2) +(x^(2) -1)^(2)


(x^(4) +2*x^(2)+1) =(4*x^(2))+(x^(4) -2*x^(2)+1)


(x^(4) +2*x^(2)+1) =(x^(4) +2*x^(2)+1) ------> is ok

that means that is a right triangle

User Anant Anand Gupta
by
6.0k points